2016
DOI: 10.1002/2015jc011620
|View full text |Cite
|
Sign up to set email alerts
|

The life cycle of a coherent Lagrangian Agulhas ring

Abstract: Abstract. We document the long-term evolution of an Agulhas ring detected from satellite altimetry using a technique from nonlinear dynamical systems that enables objective (i.e., observer-independent) eddy framing. Such objectively detected eddies have Lagrangian (material) boundaries that remain coherent (unfilamented) over the detection period. The ring preserves a quite compact material entity for a period of about 2 years even after most initial coherence is lost within 5 months after detection. We attrib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 31 publications
5
53
1
3
Order By: Relevance
“…Interactions with such topographic features are not surprising given that the vertical extent of the eddies inferred from the profiles of density anomalies was deeper than 1,500 m. The loss of volume induced by such interactions is consistent with results by Frenger et al () who showed that bottom interactions are one of the most important processes to dissipate mesoscale energy in the Southern Ocean. Between the two ridges the eddies showed reduced volume losses (<0.5 × 10 13 m 3 ), as observed in Froyland et al () and Wang et al (). Other studies (Doglioli et al, ; van Sebille et al, ) have reported larger volume losses.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Interactions with such topographic features are not surprising given that the vertical extent of the eddies inferred from the profiles of density anomalies was deeper than 1,500 m. The loss of volume induced by such interactions is consistent with results by Frenger et al () who showed that bottom interactions are one of the most important processes to dissipate mesoscale energy in the Southern Ocean. Between the two ridges the eddies showed reduced volume losses (<0.5 × 10 13 m 3 ), as observed in Froyland et al () and Wang et al (). Other studies (Doglioli et al, ; van Sebille et al, ) have reported larger volume losses.…”
Section: Discussionsupporting
confidence: 75%
“…The ∼0.5 × 10 13 m 3 of water advected by eddy B12 west of 30°W corresponds to ∼33% of the initial volume of the eddy after the Mid‐Atlantic Ridge, and to ∼12.5% of the initial combined volume of eddies AN1 and AS2 east of the Walvis Ridge. These percentages are lower than those found by Froyland et al () and Wang et al (), but the difference can be mostly explained by the depth variation in eddy volume, which was not considered in those studies.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Using different eddy detection methods, several authors have attempted to reconstruct and analyze Agulhas Rings trajectories in and across the South Atlantic (e.g., Byrne et al, ; Gordon & Haxby, ; Souza, de Boyer Montégut, Cabanes, & Klein, ; Wang et al, ). In the published studies, most reconstructions of the trajectories of Agulhas Rings leaving the Cape Basin are identified initially well within the Cape Basin and not at the Agulhas Current Retroflection where they are believed to originate (e.g., Byrne et al, ; Guerra et al, ; Souza, de Boyer Montégut, Cabanes, & Klein, ; Wang et al, , ). Taking into account the separation of an eddy into smaller structures, to which, in what follows, we will refer to as an eddy splitting event, Dencausse et al () tracked the Agulhas Rings formed in the Agulhas Retroflection area and entering the Cape Basin.…”
Section: Introductionmentioning
confidence: 99%